A novel low cost bidirectional transmission coherent passive optical network system - Shunli QIU; Yi YANG; Rong HU (Dianxin kexue)
Based on the coherent optical reception technology,a cost-effective structure for the optical network unit (ONU) transceivers in ultra-dense wavelength division multiplexing passive optical network using a single directly modulated laser (DML)was proposed.To reduce the number of required light sources,only one DML was used in both upstream and downstream links.By experimental investigations,the impacts of driving amplitude and bias current on DML's performance were analyzed.Meanwhile,the impact of frequency spacing between upstream and downstream signal and the Rayleigh backscattering interference on system performance were investigated.The method has better performance of system receiving and can effectively reduce the cost and complexity of coherent passive optical network system.